ANALISIS ECONOMIC ORDER QUANTITY (EOQ) DALAM PERSEDIAAN BAHAN BAKU UNTUK MENINGKATKAN EFISIENSI BIAYA PRODUKSI PADA UD. JUARA DESA KALIBAGOR DI KECAMATAN SITUBONDO - Ahmad Hafas Rasyidi; Ristiana Nurul Hidayah (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2017)
Economic Order Quantity analysis method can increase the effort to bias to manage the inventory well, in order to have the optimal inventory possible for smooth operation of business entity in the amount, time and quality of the right and with the lowest cost. However, based on preliminary observations it turns out raw material inventory at UD. Champion is not well planned so that the existing raw material inventory is less than optimal and the production process can not run smoothly. This is due to lack of raw material inventory. The design of research is focused on how to find out the comparison of the efficiency level of the company's financial condition. This research has no population and sample but direct the whole case of inventory and use of raw materials at UD Champion of Kalibagor Village Situbondo beside that there are also other tile businessman in Kalibagor Village as many as 19 businessmen. Quantity of ordering of optimal raw materials according to Economic Order Quantity (EOQ) during June 2017 until May 2018 at UD. Champion of Kalibagor village, Situbondo sub-district is bigger than company policy with frequency of order which is smaller than company policy. By using EOQ method, quantity ordering of expensive tile raw material equal to 9907 with frequency of ordering 98 times while company policy equal to 9,300 with frequency 357 times and at order of cheap tile raw material by using EOQ method gets quantity ordering 6,839 with frequency 83 times while with company policy amounted to 6245 with frequency 357 times. Total inventory cost by using EOQ Method on expensive tile raw material amounted to Rp3,346,850, while with company policy of Rp10,325,400. So we can get profit by using EOQ which produce Total Cost which is cheaper compared to that owned by company with difference Rp6.978.550. Total inventory cost by using EOQ Method on cheap bakugenteng material amounted to Rp2.705.812, while with the company policy of Rp10.325.400. So we get the advantage by using EOQ that produces Total Cost which is cheaper than that owned by the company with the difference ofRp7.619.588.